2008
DOI: 10.1111/j.1745-4549.2007.00170.x-i1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Defatted Melon (Citrullus Vulgaris Schrad.) Kernel Flour Supplementation on the Storage Stability and Microbiological Quality of Refrigerated Beef-Based Sausages

Abstract: The effects of defatted melon (Citrullus vulgaris Schrad.) seed kernel flour supplementation and cold storage on the storage stability and microbial quality of beef‐based sausages were evaluated using beef/melon blend ratios of 100:0, 90:10, 80:20, 70:30 and 60:40. Sausage samples were stored at 4 ± 1C for a 28‐day period during which the samples were periodically taken and subjected to chemical and microbiological analyses. One hundred percent beef sausage served as control. Parameters measured were thiobarbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…No significant differences with control on the overall acceptability and appearance were found at the 20% substitution level. The same authors found that, after two and four weeks of storage, the thiobarbituric acid reactive substance (TBARS) values were significantly lower for the sausages with substitution levels above 20% [ 64 ]. Low-fat beef patties where the meat was substituted with plum puree (5–15%) showed an increase in the cooking yield and redness of the patties but a decrease in WHC, lightness and yellowness [ 52 ].…”
Section: Meat Extendersmentioning
confidence: 99%
“…No significant differences with control on the overall acceptability and appearance were found at the 20% substitution level. The same authors found that, after two and four weeks of storage, the thiobarbituric acid reactive substance (TBARS) values were significantly lower for the sausages with substitution levels above 20% [ 64 ]. Low-fat beef patties where the meat was substituted with plum puree (5–15%) showed an increase in the cooking yield and redness of the patties but a decrease in WHC, lightness and yellowness [ 52 ].…”
Section: Meat Extendersmentioning
confidence: 99%
“…Additionally, meat in beef sausages was replaced with melon flour made from defatted melon kernels at substitution levels ranging from 10 to 40%. As the substitution levels increased, the sausages' yield, WHC, and sensory qualities improved [10]. When plum puree (5-15%) was used to substitute low-fat beef patties, the cooking yield and redness were increased, but the WHC, lightness, and yellowness were significantly reduced [11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of plant material in the meat industry as a source of functional compounds has been reported in numerous studied: the use of tomato pomace extract mixed with coriander essential oil (13); the use of celery powder, purple sweet potato powder, red gardenia powder, and paprika and blueberry (14); the application of powered parsley extract in mortadella type sausage (15); and the application of melon grain flour to beef sausages (16). However, the literature does not contain studies on the use of bioactive compounds obtained from guava epicarp and their application in meat products in order to reduce nitrite levels.…”
Section: Introductionmentioning
confidence: 99%